Platform-Mediated Managerial Reconfiguration in Primary School Administration through Google Workspace Integration - Nasywa Rosyida; Afiful Ikwan; Halil Yavuz Ezginci (Yayasan Centre for Studying and Milieu Development of Indonesia (CESMiD), 2026)
This study examines how Google Workspace integration reconfigures school administration in the context of an Indonesian primary school. While previous research on educational technology has largely focused on instructional innovation and digital learning, less attention has been given to how digital platforms reshape administrative governance and managerial functions at the school level. Addressing this gap, this study explores how Google Workspace mediates the reconfiguration of planning, organizing, directing, and controlling practices in primary school administration. A qualitative case study design was employed at SDN Banjarejo, Madiun City, Indonesia. Data were collected through semi-structured interviews with one principal, eight teachers, and two administrative staff, supported by non-participant observations and document analysis. The data were analyzed using thematic analysis through data condensation, data display, and conclusion drawing. The findings show that Google Workspace transforms planning into a continuous and data-informed process, organizing it into platform-mediated coordination, directing it into distributed digital leadership, and controlling it through real-time embedded accountability. These transformations indicate that digital platforms function not merely as administrative tools but as organizational infrastructures that reshape managerial practices and governance routines. Theoretically, this study contributes the concept of platform-mediated managerial reconfiguration to explain how digital transformation alters the logic, temporality, and coordination of school administration. In practice, the findings highlight the importance of leadership support, digital competence, a collaborative culture, and infrastructure readiness in sustaining digitally based school governance.